Spatial issues in social work education in Chile: curriculum analysis of universities and professional institutes. - Saravia-Cortés, Felipe; Orellana-Bravo, Víctor; Díaz, Francisca; Carrasco, María Luisa (Social Work Education, 2025)
In response to the growing use of spatial concepts in social work, this article addresses their incorporation in the curriculum of undergraduate programmes and the differences among diverse types of higher education institutions. The aims were 1) to identify how spatial issues are incorporated in social work curriculums in Chile and 2) to compare how this incorporation is made in social work programmes in different higher education institutions. The method was a quantitative and descriptive analysis of the curricula of the totality of the programmes in the country (N = 45). We defined 11 concepts to search: community, spatial concepts (territory, environment, place, space), spatial phenomena (city, rural, housing), and social concepts associated with spatial issues (networks, poverty, citizenship). The results show that community is the most relevant concept. Nevertheless, when viewed collectively, spatial concepts hold similar significance. However, there are noticeable differences in how different higher education institutions use spatial concepts. Professional institutes often overlook spatial concerns compared to universities. We recommend regulating social work education to incorporate a minimum curriculum that addresses these issues. Further research is needed to evaluate course content, references, and scientific publications in Chilean social work.